Land-Use Intensity Rather Than Plant Functional Identity Shapes Bacterial and Fungal Rhizosphere Communities - Schöps, Ricardo; Goldmann, Kezia; Herz, Katharina; Lentendu, Guillaume; Schöning, Ingo; Bruelheide, Helge; Wubet, Tesfaye; Buscot, François (Frontiers in Microbiology, 2018)
The rhizosphere encompasses the soil surrounding the surface of plants’ fine roots. Accordingly, the microbiome present is influenced by both soil type and plant species. Furthermore, soil microbial communities respond to land-use intensity due to the effects on soil conditions and plant performance. However, there is limited knowledge about the impact of grassland management practices under field conditions on the composition of both bacteria and fungi in the rhizosphere of different plant functional groups. In spring 2014 we planted four phytometer species, two forbs (Plantago lanceolata, Achillea millefolium) and two grasses (Dactylis glomerata, Arrhenatherum elatius) into 13 permanent experimental grassland plots, differing in management. After six months, rhizosphere and bulk soil associated with the phytometer plants were sampled, microbial genomic DNA was extracted and bacterial 16S and fungal ITS rDNA were sequenced using Illumina MiSeq. Our study revealed that the rhizosphere microbial community was more diverse than the bulk soil community. There were no differences in microbial community composition between the two plant functional groups, but a clear impact of root traits and edaphic conditions. Land-use intensity strongly affected plant productivity, neighboring plant richness and edaphic conditions, especially soil C/N ratio, which in turn had a strong influence on root traits and thereby explained to large extent microbial community composition. Rhizosphere microbes were mainly affected by abiotic factors, in particular by land-use intensity, while plant functional type had only subordinate effects. Our study provides novel insights into the assembly of rhizosphere bacterial and fungal communities in response to land-use intensity and plant functional groups in managed grassland ecosystems.